The Relationship of Consumer Attitude and Government Regulations Towards Online Gambling Behavior in The Philippines - Alexis Devera Lamoste; Yuliana Riana Prasetyawati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
The Philippine gambling industry, and particularly online gaming, has recently emerged as a major driver of the country’s economy. The rise of this controversial industry has become a cause of concern for many Filipino citizens. For the past two decades, Business Process Outsourcing (BPO) has been a major driver of the Philippine economy. However, a new sector of the economy has emerged that appears poised to take over traditional BPOs: online gambling. With the emergence of online gambling, any citizen can simply log into a website and they can play the usual casino games like poker, roulette, and slot machines or even sports betting. Online gambling is just like having a wallet in your pocket right now and just waiting for the money to come in, you just pull out your cellphone and you gamble already right away, that easy. Technically, engaging in online gambling is legal unless operated by a Philippine-licensed offshore company. Unlike other countries, the Philippines does not have strict mandates against gambling. The research aims to cover if consumer attitude and government regulations are significantly proportion with the effect of online gambling behavior. Adding to that, the researcher has added an intervening variable which is promotional ads if it has a direct impact adopting online gambling behavior. By using a quantitative analysis, the study recorded 100 respondents residing in the Philippines and studying their opinion towards this new addictive behavior relating to money. The materials and resources collected have concluded that consumer attitude and government regulations have significant impact towards this unlikely behavior, while promotional ads remain irrelevant.